2020
DOI: 10.3390/ijerph17103643
|View full text |Cite
|
Sign up to set email alerts
|

Foot Health Status Questionnaire (FHSQ) in Spanish People with Type 2 Diabetes Mellitus: Preliminary Values Study

Abstract: Background and objectives: Type 2 Diabetes Mellitus (T2DM) is a chronic disease characterized by hyperglycemia. T2DM affects millions of people, and has a lot of complications such as impaired sensation in the feet. Moreover, it is important to know the health of the feet of people with T2DM. The aim of this study is to know the preliminary values of the Foot Health Status Questionnaire (FHSQ) in people with T2DM. Materials and Methods: A total of 87 patients with T2DM with an average age of 65.56 years, divid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 22 publications
1
3
0
2
Order By: Relevance
“…Previous studies have explored the impact of chronic medical conditions and different foot health and function parameters on general health, physical and social function, and QoL. Many of these studies have discussed chronic medical conditions such as diabetes [20,26,27], obesity [20], osteoarthritis [27], hemophilia [28], and even physiological changes in pregnancy [29] and menopause [30] or various foot diseases [2,12,20,31], presenting with pain or foot dysfunction that ultimately and negatively impacts a person's QoL. This could be avoided if those causes or risk factors are addressed early and managed, which will help to improve general health, QoL, and ultimately autonomy.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have explored the impact of chronic medical conditions and different foot health and function parameters on general health, physical and social function, and QoL. Many of these studies have discussed chronic medical conditions such as diabetes [20,26,27], obesity [20], osteoarthritis [27], hemophilia [28], and even physiological changes in pregnancy [29] and menopause [30] or various foot diseases [2,12,20,31], presenting with pain or foot dysfunction that ultimately and negatively impacts a person's QoL. This could be avoided if those causes or risk factors are addressed early and managed, which will help to improve general health, QoL, and ultimately autonomy.…”
Section: Discussionmentioning
confidence: 99%
“…Examining the health of the feet in patients with systemic diseases such as type II diabetes mellitus has become a focus of research,. Thus, in the investigation by Domínguez-Muñoz et al [ 29 ], it was observed that the dimensions of general foot health, general health and vigor show a medium level value. These data could be useful to compare the health status of the foot in people with type II diabetes mellitus who attend primary care centers, in the same way as the validated RADAI-F5 questionnaire in people with rheumatoid arthritis.…”
Section: Discussionmentioning
confidence: 99%
“…These data could be useful to compare the health status of the foot in people with type II diabetes mellitus who attend primary care centers, in the same way as the validated RADAI-F5 questionnaire in people with rheumatoid arthritis. It must be highlighted that Domínguez-Muñoz et al did not perform a cross-cultural adaptation of previous reliability, which adds importance to the present investigation in terms of reliability [ 29 ]. There are other cross-cultural adaptations of questionnaires without reliability tests or assessments of clinimetric characteristics into Spanish [ 30 ], but the authors of this research think that both studies are necessary to be able to use the questionnaires in clinical settings and research.…”
Section: Discussionmentioning
confidence: 99%
“…Bu form araştırmacı tarafından literatür doğrultusunda hazırlandı. 9,10,[19][20][21] Formun birinci bölümünde; yaş, cinsiyet, eğitim, çalışma ve ekonomik durumu, yaşadığı yer, sigara kullanma durumunun değerlendirildiği sorular yer almaktadır. İkinci bölümde; hastalık süresi, ek kronik hastalık, diyabete bağlı komplikasyon, Hemoglobin A1c (HbA1c) değeri (hastaneye gelişi sırasında hekim kontrolünde istenen HbA1C değeri dikkate alındı) ve antropometrik ölçümler (boy, kilo, Beden Kütle İndeksi-BKI ve sistolik ve diyastolik kan basıncı), ülser öyküsü, kan şekeri takibi, egzersiz yapma, ayağın muayene edilme durumu, sağlık kontrolü, beslenme düzenine uyma ve diyabette ayak bakımı eğitimi alma, ayak sorununa çözüm arama şekline ilişkin sorular yer almaktadır.…”
Section: Tanıtıcı öZellikler Formuunclassified
“…9,10,11,24,25 Tip 2 diyabetli bireylerle yapılan benzer bir çalışmada, HbA1c değeri yüksek olan bireylerin istatistiksel açıdan daha fazla ayak sorunu yaşadığı belirlenmiştir. 21,30 Literatürde HbA1c değerinin yüksekliği, diyabetik ayak ve ampütasyon açısından risk faktörlerinden biri olduğu gösterilmiştir. 30,31 Bu çalışma sonuçlarının literatür ile paralel olduğu olduğu söylenebilir.…”
Section: Ayak öZ Bakım Aktiviteleri Formuunclassified